Analysis of factors influencing surface settlement during shield construction of a double-line tunnel in a mudstone area - Yuan, Chengwang; Zhang, Min; Ji, Shengcai; Li, Jiwei; Jin, Lihaolin (Scientific reports, 2022)
Urban rail transit is widely used in major cities worldwide due to its high efficiency, safety, and environmental friendliness. Shield construction has a fast excavation speed and a negligible impact on ground transportation; thus, it is the preferred construction method for urban rail transit tunnels. Mudstone is a widely distributed soft rock characterized by large deformation, low strength, and significant rheological differences in different areas. Mudstone causes problems in the design and construction of subways. This paper uses finite element analysis to establish a three-dimensional numerical model of a double-line tunnel in a weathered mudstone area and analyze the influence of the stratum, design, and construction parameters on surface settlement and deformation during asynchronous and simultaneous shield construction. The research results show that the lateral surface settlement curve obtained from the simulation is consistent with the measured data, demonstrating the reliability and feasibility of the three-dimensional numerical model. The surface settlement is affected by the deformation modulus, cohesion, and the angle of internal friction, and the deformation modulus has the most significant impact. The surface settlement decreases as the buried depth of the tunnel or the distance between the two center lines of the two tunnels increases. As the buried depth of the double-lane tunnel decreases or the distance between the two center lines of the two tunnels increases to a certain value, the lateral surface settlement curve exhibits two peaks. The surface settlement shows a decreasing trend with an increase in the thrust of the shield machine and an improvement in the grouting quality. However, excess grouting pressure causes surface uplift and a subsequent increase in surface subsidence.